Anaesthesia, Pain, Intensive Care and Emergency Medicine — A.P.I.C.E. Proceedings of the 10th Postgraduate Course in Critical Care Medicine Trieste, Italy — November 13–19, 1995 - Gullo, Antonino (Springer Milan, 1996)
This critical care medicine book substantially differs from others due to the range of peculiarities that characterize it. Since it deals with acute patients in critical conditions, this is, as it were, a 'borderline'book,in the sense that it is intended for those, who, in their activity, need a continuous and in-depth interdisciplinary approach to optimize the quality of the treatments offered to critically-ill patients. This book helps to have a better understanding of the current limits of human intervention and aims at supplying updated guidelines; in particular, it is intended for those who, although having to guarantee continuity and top-quality therapies, must decide when and why the collaboration with and intervention by experts is necessary
Keywords: Intensive / Critical Care Medicine; Anesthesiology; Critical care medicine; Notfalltherapie; Anästhesie; Schmerztherapie; Intensivtherapie; Konferenzschrift -- 1995 -- Triest